Evaluation of postoperative drainage necessity in posterior atlantoaxial fixation via intermuscular approach for odontoid fracture - Zhenji Xu; Ji Wu; Yong Li; Haibin Wang; Fei Chen; Bin Ni; Xuhua Lu; Qunfeng Guo (Scientific Reports)
Abstract The necessity of routinely placing closed suction wound drainage in spinal surgery has been questioned. This study aims to assess if closed suction wound drainage is necessary for posterior atlantoaxial fixation via intermuscular approach. The functional outcomes of these 40 patients who underwent posterior atlantoaxial fixation via intermuscular approach without drainage tube (Group A) were compared with that of a control group, which consisted of 68 randomly enrolled cases with posterior atlantoaxial fixation via intermuscular approach with drainage tube (Group B). Outcome assessments included American Spinal Injury Association (ASIA) scoring grade and Visual Analog Scale Score for Neck Pain (VASSNP). The postoperative analgesic consumption, the incidence of subcutaneous and surrounding ecchymosis and the time of ambulation were compared between two groups. Bone fusion was evaluated through computed tomography (CT) reconstruction. Postoperative paravertebral tissue edema was evaluated by the edema coefficient. The use of drainage tube had no significant influence on the postoperative analgesic consumption, wound ecchymosis, the time of ambulation and paravertebral tissue edema (P > 0.05). There were no statistically significant differences in the VASSNP and bone fusion rates during the follow-up period between the two groups (P > 0.05). All patients achieved ASIA grade E 3 months after surgery. No complications such as wound infection occurred in either group. Posterior atlantoaxial fixation via intermuscular approach does not necessitate postoperative drainage tube placement if there is no accidental vascular injury or excessive muscle bleeding occurs intraoperatively.